Exposure to psychosocial risk factors in the gig economy: A systematic review - Pierre Bérastégui (European Trade Union Institute (ETUI), 2021)
The 'gig economy' refers to a market system in which companies or individual requesters hire workers to perform short assignments. These transactions are mediated through online labour platforms, either outsourcing work to a geographically dispersed crowd or allocating work to individuals in a specific area. Over the last decade, the diversity of activities mediated through online labour platforms has increased dramatically. In addition to the specific hazards associated with these different types of activities, there are also psychosocial risks related to the way gig work is organised, designed and managed. The aim of this review is to provide a comprehensive overview of these risks, identifying research gaps and strategies to address them.
Keywords: 330; gig economy; atypical employment; work design; Mental illness; job search; digital platform; Gig Economy; Atypische Beschäftigung; Arbeitsgestaltung; Psychische Krankheit; Arbeitsuche; Digitale Plattform